Management of type-I gastric neuroendocrine neoplasms: A 10-years prospective single centre study. Issue 7 (July 2022) - Esposito, Gianluca; Cazzato, Maria; Rinzivillo, Maria; Pilozzi, Emanuela; Lahner, Edith; Annibale, Bruno; Panzuto, Francesco
Abstract: Background: This study aimed to evaluate the outcome of patients with type 1 gastric neuroendocrine neoplasia (T1gNENs) treated with different endoscopic approaches. Methods: Patients were managed with endoscopic surveillance at regular intervals. Resection was performed by forceps or cold snare in tumours < 10 mm, otherwise mucosal resection (EMR) or submucosal dissection (ESD) were done. Results: 127 T1gNENs, detected in 80 patients, were included. 87.4% of them were <5 mm, whereas 8.7% were 6–10 mm, 3.1% were 11–20 mm, and 0.8% was >20 mm. Ki67 <3%% was found in 85.8% tumours, whereas it was 3%-20% in the remaining 14.2% lesions. Noninterventional management (surveillance without radical resection) was performed in 15 patients (18.7%) with T1gNENs <5 mm. None of them underwent disease progression during follow-up. among the 65 patients treated by radical endoscopic resection, 37 patients (56.9%) had disease recurrence. 48.5% T1gNENs were removed by forceps, 16.8% by cold snare, 31.7% by EMR and 3% by ESD. The recurrence rate was similar among the different endoscopic techniques used. Conclusions: The management of T1gNENs may be planned based on tumour size. T1gNENs < 5 mm for which the initial removal is not radical could be followed up by noninterventional endoscopic surveillance.